Enhancing Algorithmic Thinking through Computational Tools: A Study on High School Computing Education - Rahmawati Rahmawati; Omar Khan; M Syahputra; Amalia Hanifa; Ediaman Sitepu (Yayasan Adra Karima Hubbi, 2024)
The importance of algorithmic thinking in modern education has grown significantly, particularly in the context of computing education in high schools. As computational tools become more accessible, their role in enhancing students' problem-solving abilities has gained considerable attention. This study investigates how computational tools can improve algorithmic thinking among high school students and their overall engagement with computing subjects. The primary objective is to assess the impact of integrating computational tools, such as programming environments and visual coding platforms, on students' development of algorithmic skills. The study adopts a mixed-methods approach, combining quantitative data from pre-and post-tests measuring algorithmic thinking skills, and qualitative data through interviews and classroom observations. A total of 150 high school students from various educational backgrounds participated in the study over one semester. The results indicate a significant improvement in students’ algorithmic thinking abilities after exposure to computational tools, particularly in areas such as problem decomposition, abstraction, and logical reasoning. Additionally, students reported higher levels of motivation and interest in computing subjects. In conclusion, the integration of computational tools in high school computing education not only enhances algorithmic thinking but also fosters greater student engagement. These findings highlight the potential of using technology to bridge the gap between theoretical concepts and practical application in computing education. Further research is encouraged to explore long-term effects and the scalability of these methods across diverse educational settings.